Festival participation as the mediator role towards emotional solidarity on destination loyalty among college students - Liu, Mengyuan; Ariffin, Hashim Fadzil; Ngelambong, Anderson (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This research aims to test festival participation as the mediator role towards relationship between emotional solidarity and destination loyalty among Chinese college students. 400 college students from Guilin, China participated in the survey by answering online questionnaires. Convenience sampling ensures that data from a specific population sample is collected more accurately. The results suggest that these festival participation have a mediating effect between the emotional solidarity of Chinese college students and the loyalty of their learning place. These findings were validated by model 4 mediation analysis, which belonged to Hayes Process Macro. The findings are expected to enrich our understanding of Chinese college students’ study destination loyalty behaviors. Provide new insights for tourism managers, practitioners, and marketers.